Efektivitas Reaktor Biogas dan Pengolahan Limbah Bioslurry Sebagai Sumber Energi Rumah Tangga Serta Hara Organik Pada Wilayah Pertanian Di Halmahera Timur - Suparman Suparman; Suryati Tjokrodiningrat; Zauzah Abdullatif; Said Hasan; Yunus Syafie; Asrul Dedy Ali Hasan (Jurnal Pertanian Khairun, 2023)
East Halmahera is the main area for developing rice and beef cattle in the North Maluku region. The cultivation of food crops and livestock production generates substantial waste which requires proper management. Precise waste management can reduce environmental pollution in agricultural areas while creating added value opportunities. Rice waste is used with cow manure to produce biogas and organic fertilizer through anaerobic digestion technology. In this research, rice waste and cow dung were used to produce biogas and organic fertilizer through anaerobic digestion. The research is a continuation of previous studies on biogas production in a laboratory setting. The study is divided into two stages: firstly, the production of biogas, and secondly, the creation of organic fertilizer from the remaining bioslurry. The performance of a Modified Profile Anaerobic Reactor biogas digester was evaluated using standard parameters such as pH, temperature, total solids, and flame duration. The nutrient content of the organic fertilizer was tested based on various parameters, including C-organic, Nitrogen (N), C/N ratio, Phosphorus (P2O5), and Potassium (K2O). The results of the research showed that a biogas reactor with a capacity of 2.200 kg produced 4.2 kg of biogas with a flame duration of 12 hours, 7 minutes, and 10 seconds. The average temperature during the process was 29°C, and the total solid organic material decomposition was 33%. Total solid processed organic fertilizer with a C/N value of 16.53, C-Organic content of 24.16%, macronutrients N 1.93%, P2O5 0.37%, and K2O of 1.75%.Keywords: biogas, organic fertilizer, rice husks, cow dung, and East Halmahera.